ICT and artistic education. (Journal of Parents and Teachers, 2014)
The artistic expression is a necessity of the human being. ICT plays an important role both in the creation and dissemination of artistic works. The article offers ICT resources for the development of artistic competence.
Keywords: ICT; plastic; arts; web resources.